2001
DOI: 10.1029/2001gl012989
|View full text |Cite
|
Sign up to set email alerts
|

Negligible direct radiative forcing of basin‐scale climate by coccolithophore blooms

Abstract: Abstract.The water-leaving radiance, defined as radiation from the sun reflected off particles in water and exiting the ocean surface back into the atmosphere and space, is often used to derive ocean-colour information from remotely sensed data. However, it is in itself a measure of the amount of solar irradiance reflected by oceanic constituents and, therefore, not available to the Earth's heat reservoir (changes in which can affect the Earth's energy balance and climate). A strong influence on the water-leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…When the plankton grow and divide at a high rate, they shed their calcium carbonate plates (liths) into the surrounding seawater [ Paasche , ]. In bloom conditions, the liths create a strong backscattering signal that can be observed by satellite remote sensing [ Balch et al ., ], and can have a significant local effect on radiative forcing [ Gondwe et al ., ]. Recent work has facilitated the routine identification of coccolithophore blooms in the North Atlantic [ Shutler et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…When the plankton grow and divide at a high rate, they shed their calcium carbonate plates (liths) into the surrounding seawater [ Paasche , ]. In bloom conditions, the liths create a strong backscattering signal that can be observed by satellite remote sensing [ Balch et al ., ], and can have a significant local effect on radiative forcing [ Gondwe et al ., ]. Recent work has facilitated the routine identification of coccolithophore blooms in the North Atlantic [ Shutler et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a direct negative forcing of climate (i.e., a reduction in the amount of incoming solar radiation absorbed by the ocean system) was believed to be caused by an increase in the amount of solar radiation returned to the atmosphere and space through backscattering by spatially extensive and highly reflective coccolithophore blooms in the ocean [e.g., Tyrell et al , 1999]. However, Gondwe et al [2001] have recently found this effect to be marginal and not enough to perturb global climate.…”
Section: Introductionmentioning
confidence: 99%